Morbidity and mortality among diabetic patients admitted to Mulago Hospital, Uganda - Bateganya, MH (Malawi Medical Journal, 2003)
OBJECTIVES: To document the causes of admission, clinical presentation and outcome of patients admitted with diabetes mellitus to our medical wards. SETTING: Medical wards of Mulago Hospital, teaching hospital and national referral for the government of Uganda. STUDY DESIGN: Cross-sectional descriptive non-interventional study of diabetic medical admissions. RESULTS: During the study period 129 (4.2%) patients with diabetes mellitus out of 3103 total medical admissions were admitted. The commonest cause of admission was uncontrolled diabetes (48.3%) but infections were present in 27.7% of all the study patients. The commonest infections were pneumonia (15%) and urinary tract infections (11.8%). Diabetic ketoacidosis (DKA) was a cause of admission in 9.2% of all the study subjects. Glycaemic control was satisfactory among 50.6% (HbA1c less than 7) despite 84.5% of the study subjects being hyperglycaemic at admission (mean random blood sugar 20±9.0 mmol/L). Fifty-point seven of the subjects had long term complications of diabetes at admission with hypertension (53.8%) and peripheral neuropathy (38.3%) being the commonest. There were 13 deaths (10.8%) and 61.5% of the deaths were among patients admitted with infections. The average length of hospitalisation was 9.5±4 days. CONCLUSION: The results show that the commonest causes of admission were uncontrolled diabetes and infections. The mortality rate was 10.8%.